Optical characterization of a biaxial nematic between uniaxial nematic lyotropic phases. (3rd August 2021) - Santos, O. R.; Braga, W. S.; Luders, D. D.; Sampaio, A. R.; Kimura, N. M.; Simões, M.; Palangana, A. J.
ABSTRACT: The biaxial nematic ( N B ) phase bordered by two uniaxial nematic (discotic – N D and calamitic – N C ) phases and the one between N D phases are studied in potassium laurate ( KL ), decanol ( DeOH ) and D 2 O mixture using conoscopic images. The sequences of phases ( N D → N B + → N B − → N C and N D → N B + → N D ) were optically characterized, where N B + and N B − are the biaxial positive and biaxial negative nematic phases, respectively. A new sequence of phases ( N D → N B + → N B − → N B + → N D ) found in one line of the phase diagram positioned close to the interface with the N C phase was also optically confirmed through conoscopic images. The N B + ( N B − ) → N B − ( N B + ) transition point was determined by means of image processing. In this review work, we emphasize the relevance of the optical characterization of an N B − phase inherent to the nature of this lyotropic material.